Green buildings and the law - Adshead, Julie (Abingdon, Oxon : Spon Press, 2011)
'In countries such as the UK, the energy used in constructing, occupying and operating buildings represents approximately 50% of greenhouse gas emissions. Pressure to improve the environmental performance of buildings during both construction and occupancy, particularly to reduce carbon emissions from buildings, has become intense.Understandably, legislation and regulation are driving green development and compliance. And this is happening in a wide variety of ways. This review of the law in key jurisdictions for the research community, lawyers, the construction industry and government examines some of the mechanisms in place from the more traditional building regulation controls to green leases and the law relating to buildings and their natural environment. Members of the CIB TG69 research group on green uildings and the Law review aspects of the law relating to green development in a range of jurisdictions'--Provided by publisher.
'Legislation and regulation are driving green development and compliance in a wide variety of ways. This international review of the law in key jurisdictions for the research community, lawyers, the construction industry and government examines some of the mechanisms in place - from the more traditional building regulation controls to green leases and the law relating to buildings and their natural environment'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Sustainable buildings -- Law and legislation; Sustainable buildings -- Design and construction